Regulating Bacterial Behavior within Hydrogels of Tunable Viscoelasticity. Issue 17 (11th April 2022) - Bhusari, Shardul; Sankaran, Shrikrishnan; del Campo, Aránzazu
Abstract: Engineered living materials (ELMs) are a new class of materials in which living organism incorporated into diffusive matrices uptake a fundamental role in material's composition and function. Understanding how the spatial confinement in 3D can regulate the behavior of the embedded cells is crucial to design and predict ELM's function, minimize their environmental impact and facilitate their translation into applied materials. This study investigates the growth and metabolic activity of bacteria within an associative hydrogel network (Pluronic‐based) with mechanical properties that can be tuned by introducing a variable degree of acrylate crosslinks. Individual bacteria distributed in the hydrogel matrix at low density form functional colonies whose size is controlled by the extent of permanent crosslinks. With increasing stiffness and elastic response to deformation of the matrix, a decrease in colony volumes and an increase in their sphericity are observed. Protein production follows a different pattern with higher production yields occurring in networks with intermediate permanent crosslinking degrees. These results demonstrate that matrix design can be used to control and regulate the composition and function of ELMs containing microorganisms. Interestingly, design parameters for matrices to regulate bacteria behavior show similarities to those elucidated for 3D culture of mammalian cells. Abstract : Understanding bacterial behavior in confinement is of great interest for designing engineered living materials or studying biofilms. In this work, a unique hydrogel platform, whose viscoelastic properties can be tuned by varying the extent of stabilizing crosslinks, is developed to demonstrate that the growth and metabolism of encapsulated bacteria can be regulated by mechanical restrictions imparted by the matrix.